Rabies surveillance in bats in Northwestern State of São Paulo - Daiene Karina Azevedo Casagrande; Ana Beatriz Botto de Barros da Cruz Favaro; Cristiano de Carvalho; Mileia Ricci Picolo; Janaína Camila Borges Hernandez; Monique Serra Lot; Avelino Albas; Danielle Bastos Araújo; Wagner André Pedro; Luzia Helena Queiroz (Revista da Sociedade Brasileira de Medicina Tropical, 2014)
Introduction Rabies is an important zoonosis that occurs in mammals, with bats acting as Lyssavirus reservoirs in urban, rural and natural areas. Rabies cases in bats have been recorded primarily in urban areas in Northwestern State of São Paulo since 1998. This study investigated the circulation of rabies virus by seeking to identify the virus in the brain in several species of bats in this region and by measuring rabies-virus neutralizing antibody levels in the hematophagous bat Desmodus rotundus. Methods From 2008 to 2012, 1,490 bat brain samples were sent to the Universidade Estadual Paulista (UNESP) Rabies Laboratory in Araçatuba, and 125 serum samples from vampire bats that were captured in this geographical region were analyzed. Results Rabies virus was detected in the brains of 26 (2%) of 1,314 non-hematophagous bats using the fluorescent antibody test (FAT) and the mouse inoculation test (MIT). None of the 176 hematophagous bat samples were positive for rabies virus when a virus detection test was utilized. Out of 125 vampire bat serum samples, 9 (7%) had levels of rabies virus neutralization antibodies (RVNAs) that were higher than 0.5IU/mL; 65% (81/125) had titers between 0.10IU/mL and 0.5IU/mL; and 28% (35/125) were negative for RVNAs using the simplified fluorescent inhibition microtest (SFIMT) in BHK21 cells. The observed positivity rate (1.7%) was higher than the average positivity rate of 1.3% that was previously found in this region. Conclusions The high percentage of vampire bats with neutralizing antibodies suggests that recent rabies virus exposure has occurred, indicating the necessity of surveillance measures in nearby regions that are at risk to avoid diffusion of the rabies virus and possible rabies occurrences.